Universalism and particularism at Sodom and Gomorrah: essays in memory of Ron Pirson - Lipton, Diana; Pirson, Ron (Ancient Israel and its literature, 2012)
Remembering Ron Pirson, by his life-partner Petra Thijs -- Ron Pirson: memories of a former colleague Pierre Van Hecke -- Ron Pirson: publications -- The eternal liminality of Lot: paying the price of opposing the particular in the Sodom narrative William John Lyons -- The limits of intercession: Abraham reads Ezekiel at Sodom and Gomorrah Diana Lipton -- Changing God's mind: Abraham versus Jonah T. A. Perry -- Why did God choose Abraham? Responses from medieval Jewish commentators Amira Meir -- Outcry, knowledge, and judgment in Genesis 18-19 Ellen J. Van Wolde -- Legal and ethical reflections on Genesis 18 and 19 Calum Carmichael -- Keeping the way of YHWH: Righteousness and justice in Genesis 18-19 Megan Warner -- Was Lot a good host? Was Lot saved from Sodom as a reward for his hospitality? Yitzhak (Itzik) Peleg -- Hospitality compared: Abraham and Lot as hosts Jonathan D. Safren -- Hospitality and hostility: reading Genesis 19 in light of 2 Samuel 10 (and vice versa) Nathan MacDonald -- Beyond particularity and universality: reflections on Shadal's commentary to Genesis 18-19 Harlan J. Wechsler -- Does Lot know about Yada'? Ron Pirson